PARAINEN PEARL SHIPPING LTD v KRISTIAN GERHARD JEBSEN SKIPSREDERI AS. Issue 3 (20th September 2019) - ,
Abstract: H1 Patents – European patents – Declaration of non-infringement – Ships – System "for" unloading powdery cargo – Cement handling – Patentee's ship equipped with patented system declared total loss – Ship re-floated – Title to ship passing to third party – Patented system not operational – Restrictions as to future use – Ship re-sold – Patentee not exercising option to purchase – Later purchasers putting system back into operation – Whether work done amounting to making repair or replacement – Exhaustion of rights – Implied licence – Estoppel